1985
DOI: 10.1007/bf01871518
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-dependent membrane impedance inChara corallina estimated by Fourier analysis

Abstract: The white noise method of measuring membrane impedance has been applied to internodal cells of Chara corallina. Fourier analysis of a white noise transmembrane current signal and the voltage response has been used to obtain the frequencydependent impedance of the in-series combination of the plasmalemma and tonoplast membranes. The results are similar to those of other workers who have measured membrane impedances by different techniques. At very low frequencies the equivalent capacitance of the membrane treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
2
9
1
Order By: Relevance
“…This means that the voltage noise PSD sampled from the cell after treatment with DCCD (Fig. 2a) will be larger relative to the control PSD than if correction had been made for membrane impedance as described in (20)(21)(22), but it is still clear that DCCD strongly inhibited the LFSC. These results, along with the studies quoted above (2, 6, 7), imply that DCCD inhibits the active proton pump directly.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This means that the voltage noise PSD sampled from the cell after treatment with DCCD (Fig. 2a) will be larger relative to the control PSD than if correction had been made for membrane impedance as described in (20)(21)(22), but it is still clear that DCCD strongly inhibited the LFSC. These results, along with the studies quoted above (2, 6, 7), imply that DCCD inhibits the active proton pump directly.…”
Section: Discussionmentioning
confidence: 97%
“…The experimental arrangement for sampling voltage noise signals from internodes of Chara corallina has been described previously (21,22 described by Hope and Walker (4), which will henceforth be referred to as CPW. The CPW was supplemented with the inhibitors listed in Table I.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were cultured in the laboratory in fiberglass tanks as described previously ( 19). Figure 1 illustrates schematically the experimental arrangement used to sample voltage noise signals.…”
Section: Methodsmentioning
confidence: 99%
“…The CPW was buffered by adding 5 mm Tes and titrating to pH 7.5 with 1 M NaOH. Other pH values were obtained using 5 mm concentrations of the buffers described in Ross et al (19).…”
Section: Methodsmentioning
confidence: 99%
“…It has been observed in samples as different as crystalline and amorphous semiconductor devices, [1][2][3][4][5][6][7][8][9] organic compounds, [10][11][12][13][14] composite materials/nanomaterials, 9,15-22 electrochemical cells, [23][24][25] geological samples, 26 biological membranes, [27][28][29] and even moist surfaces. 30 Furthermore, it has been shown that NCs can originate at interfaces as well as in the bulk of the materials.…”
Section: Introductionmentioning
confidence: 99%